2013
DOI: 10.1007/s00204-013-1017-5
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-exposed developing rats display motor deficits and striatal oxidative stress that are reversed by Trolox

Abstract: While manganese (Mn) is essential for proper central nervous system (CNS) development, excessive Mn exposure may lead to neurotoxicity. Mn preferentially accumulates in the basal ganglia, and in adults it may cause Parkinson's disease-like disorder. Compared to adults, younger individuals accumulate greater Mn levels in the CNS and are more vulnerable to its toxicity. Moreover, the mechanisms mediating developmental Mn-induced neurotoxicity are not completely understood. The present study investigated the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 106 publications
3
48
1
3
Order By: Relevance
“…These results represent the first evidence that developmental exposure to Mn can lead to long-lasting effects toward striatal GSH levels, observed during adulthood. Furthermore, oxidative stress may be related to motor damage, since co-treatment with Mn and the antioxidant Trolox improved the performance exhibited in the rotarod (Cordova et al, 2012(Cordova et al, , 2013. However, additional studies using antioxidants would be necessary to demonstrate whether oxidative stress contributes to motor impairment in Mn exposed animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results represent the first evidence that developmental exposure to Mn can lead to long-lasting effects toward striatal GSH levels, observed during adulthood. Furthermore, oxidative stress may be related to motor damage, since co-treatment with Mn and the antioxidant Trolox improved the performance exhibited in the rotarod (Cordova et al, 2012(Cordova et al, , 2013. However, additional studies using antioxidants would be necessary to demonstrate whether oxidative stress contributes to motor impairment in Mn exposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…with saline (0.9% NaCl; controls) or MnCl 2 5, 10, 20 mg/kg for five consecutive days (PND8-12) as previously described (Rocha et al, 1995;Cordova et al, 2012). The dose regimen was chosen based on previous studies (Cordova et al, 2013) in an attempt to mimic Mn exposures derived from TPN, which have been associated with significant increase in brain Mn levels both in adults and in children (Ejima et al, 1992;Fell et al, 1996;Nagatomo et al, 1999).…”
Section: In Vivo Mn Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnification 9400 a previous study (Oszlánczi et al 2010), our findings demonstrated that Mn significantly reduced spontaneous activity. Excessive Mn accumulation in the striatum can result in a neurological syndrome, which can further lead to motor abnormalities (Cordova et al 2013). In addition, we evaluated the extent of injuries by HE staining.…”
Section: Discussionmentioning
confidence: 99%
“…22,65 Moreover, striatal activation of both ERK1/2 in response to Mn exposure at PN8-12 and p38 MAPK in response to more prolonged exposure (PND8-27), in a manner dependent of oxidative stress production, were reported. 22,65 Consistent with this temporal effect and other in vitro and in vivo studies, 38,47 it is plausible that in vivo Mn exposure may lead to Immature rats treated at PND8-12 or PND8-27 with 20 mg kg À1 Mn displayed an increment of striatal Akt phosphorylation by undefined mechanism but apparently independent of oxidative stress. Moreover, striatal activation of both ERK1/2 in response to Mn exposure at PN8-12 and p38 MAPK in response to more prolonged exposure (PND8-27) was dependent on reactive oxygen species (ROS) production, since the antioxidant Trolox abrogated this effect.…”
Section: Alteration In Mapk and Akt Signaling Induced By Manganesementioning
confidence: 97%